Central serous chorioretinopathy: An update on risk factors, pathophysiology and imaging modalities. (November 2020) - Kaye, Rebecca; Chandra, Shruti; Sheth, Jay; Boon, Camiel J.F.; Sivaprasad, Sobha; Lotery, Andrew
Abstract: Central serous chorioretinopathy (CSC) is a common form of vision loss, typically seen in working-age men. The pathophysiology behind CSC still eludes us, however significant advances have been made in understanding this disease over the last decade using information from genetic and cell-based studies and imaging modalities. This review aims to give an overview of the current pathophysiology hypotheses surrounding CSC in addition to future directions in cellular work from human induced pluripotent stem cell derived choroidal endothelial cells from CSC patients. Furthermore, this review will provide the reader with an update on the clinical aspects of CSC including risk factors, diagnostic challenges and findings from multimodal imaging.